Preparation and characterization of high melt strength thermoplastic polyester elastomer with different topological structure using a two-step functional group reaction. (28th September 2019) - Jiang, Rui; Chen, Yichong; Yao, Shun; Liu, Tao; Xu, Zhimei; Park, Chul B.; Zhao, Ling
Abstract: Long-chain branched (LCB) thermoplastic polyester elastomer (TPEE) could be controllably prepared by the two-step reaction of the linear TPEE with triglycidyl isocyanurate (TGIC) and 2, 2′-bis(2-oxazoline) (2, 2′-BOZ) together in different sequences to improve their rheological properties and foaming ability. All of the modified TPEEs reacted with TGIC first and then with 2, 2′-BOZ have more branching points and longer chains. These samples show a higher molecular weight, a broader molecular weight distribution. These samples also had a higher viscosity and modulus, a longer relaxation time, and a stronger strain-hardening effect. Moreover, the greater number of branching points accelerated the non-isothermal crystallization process. The foaming ability of the modified TPEEs was evaluated via a batch CO2 -foaming process. The LCB structure improved the melt viscoelasticity and the foaming ability remarkably. The TPEE samples with more chain branching points and longer chains had the highest cellular densities and the largest expansion ratios, with average cell diameters of 4–13 μm, cell densities of 2.0 × 10 9 –1.0 × 10 11 cells/cm 3, and expansion ratios of 2.5–14.1. Graphical abstract: Image 1 Highlights: Topological structure of long chain branched TPEEs could be controllable produced. Controlling the rheological properties of TPEE by different reacting sequences. TPEE that modified with TGIC first have better foamability.